How Stress And Gastritis Occurs In Teenagers - Prastomo Suhendro; Taufiqur Rahman; Moh Habiburrohman (SABDA EDU PRESS (SEP), 2024)
Gastritis, also known as stomach ulcers, is inflammation (swelling) of the gastric mucosa caused by irritation and infection, one of the causes of which is psychological factors or stress. In fact, people, especially teenagers, think that gastritis is only caused. The aim of this research is to determine the relationship between stress and the incidence of gastritis in teenagers at Bustanus Shibyan Islamic High School, Bulmatet Village, Karang Penang Sampang District in 2023. Method: This research design uses quantitative research methods using a cross sectional approach. The population in this study was all students at Bustanus Shibyan Islamic High School, Bulmatet Village, Karang Penang Sampang District, totaling 52 students and the sample was all students at Bustanus Shibyan Islamic High School, Bulmatet Village, Karang Penang Sampang District. The technique used is total sampling. Data was collected using a questionnaire sheet and analyzed descriptively and presented in table and narrative form. Based on the research results, it was found that the majority of respondents experienced gastritis due to moderate stress, 18 people (64%). The role of health workers, especially nurses, is needed to provide education in dealing with this problem, namely as educators who can provide information to the public about the importance of controlling stress in gastritis sufferers.